Wage structure and inequality: The role of observed and unobserved heterogeneity - István Boza (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2021)
This study aims to contribute to the literature of firms and occupations as prominent drivers of wage-inequality in multiple ways. First, we synthesize novel modelling approaches of recent studies in the field and use administrative linked employer-employee panel data from an Eastern European country, Hungary, to assess the contribution of individual, firm and job heterogeneity - and their interactions - to overall wage inequality. Consistent with earlier findings from Western Europe, Scandinavia, the US and Brazil, we show that firm heterogeneity provides around 22%, individual heterogeneity 50%, and occupational heterogeneity 8% of overall wage dispersion, with wage sorting between firms and individuals in itself explaining around 9%. Notably, around half of this contribution is accountable to observable sub-components of individual and firm wage effects. Also, the same magnitude of assortativity can be found between individuals and occupations. Utilizing unique features of our data, we compare mathematics and literature test score records of 10th grade students to their future labor market outcomes, finding a positive correlation between test scores and future firm value added, a direct evidence for assortative matching in productivity. Finally we assess sorting along observable characteristics, such as gender, education, occupation or age of workers, and the ownership of employers.
Keywords: J31; D63; I24; 330; wage inequality; wage decomposition; fixed effects; linked employer-employee data; sorting; assortative matching